LNB-TM7, a group of seven-transmembrane proteins related to family-B G-protein-coupled receptors. - Stacey, M.; Lin, H.H.; Gordon, S.; McKnight, A.J. (Trends in Biochemical Sciences, 2000)
A number of unusual seven-transmembrane molecules have recently been characterized that have significant amino acid sequence similarity within the membrane-spanning hydrophobic regions and intervening loops to members of G-protein-coupled receptor family B. However, in contrast to the family-B G-protein-coupled receptors, these molecules have unusually large N-terminal extracellular domains that contain a number of well- characterized protein modules. The range of cell types expressing these complex molecules and their potential roles in cell adhesion and signalling have become a major focus of research in a number of biological systems.